Perspectives on fair housing - Reina, Vincent J.; Pritchett, Wendell E.; Wachter, Susan M.; Morial, Marc H. (City in the twenty-first century book series., 2021)
"Title VIII of the Civil Rights Act of 1968, known as the Fair Housing Act, was the most robust piece of federal legislation aimed at stopping the systemic and severe discriminatory practices that defined the housing market at that time and through the present.This legislation has been crucial to the fight against housing discrimination but has by no means eliminated it. The compounding inequities of historic housing discrimination, and it's persistence to this day, present a serious challenge to the future of American society. This book makes the case that fair housing is a critical issue not only for those directly affected by it, but also for society more broadly, and that meaningful government intervention is required to achieve fair housing just as much now as fifty years ago"--